Reducing electrode wear ratio using cryogenic cooling during electrical discharge machining - Abdulkareem, Suleiman; Khan, Ahsan Ali; Mohamed , Konneh (Springer, 2009)
In this study, cooling effect of copper electrode on the die-sinking of electrical discharge machining of titanium alloy (Ti-6Al-4V) has been carried out. Investigation on the effect of cooling on electrode wear and surface roughness of the workpiece has been carried out. Design of experiment plan for rotatable central composite design of second order with four variables at five levels each has been employed to carry out the investigation. Current intensity (I), pulse on-time (ton), pulse off-time (toff), and gap voltage (v) were considered as the machining parameters, while electrode wear and surface roughness are the responses. Analysis of the influence of cooling on the responses has been carried out and presented in this study. It was possible to reduce electrode wear ratio up to 27% by electrode cooling. Surface roughness was also reduced while machining with electrode cooling.